Makna Kanji Yojijukugo yang Diawali Kanji Angka dan Padanannya dalam Peribahasa Indonesia - Arlianti, Hasna Imaroh Putri (KIRYOKU, 2024)
This research aims to describe the meanings of yojijukugo that begin with the kanji characters for numbers one to ten and have equivalents in Indonesian proverbs. The theory utilized in this study is the theory of semantic meaning. This research is a qualitative descriptive study. The data collection method used is a literature review method that derives information from various book sources. In this research, a comparative technique with a linking comparison method is utilized to analyze the acquired data. The results of this study show 15 yojijukugo have equivalents in Indonesian proverbs. 2 data are sourced from the Idiom Encyclopedia website, 10 data from the book "Saikin Irasuto de Wakaru Yojijukugo Jiten," and 3 data from the "Jitsuyo Kotowaza KanyoukuJiten". Yojijukugo that have the most equivalents are those started with the kanji character for number one, while those with the least is yojijukugo that start with number two, five, eight, and nine. The yojijukugo that has no equivalent is the yojijukugo that start with the kanji number six. Then some yojijukugo also have atendency of meaning that comes from Buddhism and Chinese history, while the Indonesian proverbs tend to be more about advice and etc.